Ethics and emancipation in action: concrete utopias - Dave Elder-Vass (2022)
This is an edited transcript of a keynote paper given at IACR's 2021 Annual Conference. The paper outlines a critical realist approach to critique and illustrates its application to the contemporary economy. It argues that responsible, constructive critique depends on ethics, on causal explanation, and on the development of utopian visions. Utopias are tools, and concrete utopias are not visions of whole alternative ready-made societies, but rather partial models that can be built in practice as elements of the larger social world. The argument is illustrated with three cases of digital utopianism, which help to demonstrate the practical challenges facing utopian schemes. Concrete utopias are a vehicle for combining our theoretical understandings of possibilities with an ethical analysis of needs in order to offer practical schemes for improving human flourishing.